S55 Cost-effectiveness and quality of life results from the ASTER study: endobronchial and endoscopic ultrasound vs surgical staging in potentially resectable lung cancer. (2nd December 2011) - Rintoul, R C; Annema, J T; Tournoy, K G; Dooms, C; Wheaton, E; Hughes, V; Grant, A; Griffith, G; Buxton, M; Sharples, L
Abstract : Background: We recently published clinical results of ASTER, a randomised controlled trial in which endosonography, a strategy of combined endoscopic (EUS) and endobronchial (EBUS) ultrasound (followed by surgical staging if these tests were negative for malignancy), had significantly higher sensitivity and negative predictive value than surgical staging alone for mediastinal staging in NSCLC. Here we present ASTER quality of life (QoL) and cost-effectiveness outcomes. Methods: EuroQoL EQ-5D questionnaire was performed at baseline, end of staging, 2 and 6 months post randomisation. The UK EQ-5D social tariff was applied to calculate utility values. Quality-adjusted survival was estimated using the area under the utility curve. Full resource use information was recorded for all patients and NHS 2008–2009 Reference Costs were applied. Total expected costs over 6 months were estimated by summing the resource use multiplied by its unit cost and taking the sample average for each group. Results: Of 241 randomised patients, 144 (60%) provided EQ-5D data at baseline; of these 139 (97%) were followed up at the end of staging, 132 (92%) at 2 months and 124 (86%) at 6 months. At the end of staging, those randomised to endosonography had significantly better QoL than those randomised to surgical staging (utility difference=0.11, 95%CI 0.02 to 0.19). At all other time points, there was little difference between the groups, so that quality adjusted survival over the 6 months was similar (4.1 vs 4.0 months respectively). Complete resource use data were available for 172/214 (71%) patients. Other than the number of thoracotomies performed (66% of patients in the surgical staging arm and 53% in the endosonography arm) resource use did not differ between the two groups. The endosonography group had a non-significant cost saving of £746 per patient compared to the surgical staging group. Conclusions: Given that (a) the sensitivity of endosonography was significantly higher than that of the surgical staging arm; (b) QoL post-staging was higher in the endosonography arm and (c) there is no difference in cost between the two strategies, mediastinal staging should commence with endosonography proceeding to surgical staging if there is no evidence of malignancy.